Immigrants in Polish cities: the case of Pabianice in the Łódź region - Jakóbczyk-Gryszkiewicz, Jolanta (Konwersatorium Wiedzy o Mieście, 2020)
The aim of this work is to present immigration processes in Pabianice, one of the towns in the Łódź region. Foreigners, mostly Germans, were arriving here from the beginning of the 19th century in connection with industrial development. They contributed to the growth of this city when it was becoming a major centre of the textile industry and later they and their descendants became its citizens. The second period of intensive immigration is the beginning of the 21st century after Poland’s accession to the EU. The majority of present-day immigrants are arriving from outside the EU, mainly from Ukraine and India. Those from India, who settle for a longer time, work in their wholesale clothing outlets, while Ukrainians and representatives of other nations find work in trade, catering, manufacturing and construction on a temporary basis – returning home and coming back again. Today, the residents of Pabianice appreciate the effects of the activity of both 19th century and present-day immigrants. Generally, their attitude to foreigners has been positive. Celem pracy jest prezentacja ruchów imigracyjnych w Pabianicach, które są jednym z miast regionu łódzkiego. W związku z rozwojem przemysłu cudzoziemcy przybywali tam od początków XIX w. Dzięki nim miasto rozwinęło się jako znaczący ośrodek przemysłu włókienniczego, a oni sami oraz ich potomkowie stali się jego obywatelami. Drugim okresem intensywnego napływu cudzoziemców był początek XXI w., zwłaszcza czas po wstąpieniu Polski do Unii Europejskiej (UE). W poszukiwaniu pracy do Pabianic przybyli najliczniej cudzoziemcy spoza UE, głównie z Ukrainy i z Indii. Hindusi pracują we własnych hurtowniach tkanin oraz osiedlają się na dłużej, zaś Ukraińcy i inne nacje znajdują zatrudnienie w handlu, gastronomii, przemyśle i na budowach w systemie rotacyjnym – pracują w Polsce, wracają do własnego kraju i ponownie przyjeżdżają do Polski. Mieszkańcy Pabianic dostrzegają zarówno spuściznę cudzoziemców dziewiętnastowiecznych, jak i działalność obecnych imigrantów. Ich stosunek do cudzoziemców jest na ogół pozytywny.